Do Politically Connected Firms Innovate, Contributing to Long-Term Economic Growth? - Francis, David (World Bank, Washington, DC, 2018)
This paper presents new evidence that cronyism reduces long-term economic growth by discouraging firms' innovation activities. The analysis is based on novel establishment survey data from The Arab Republic of Egypt which provides information on establishments' political connections, their innovation activities, and their access to policy privileges. The analysis finds that the probability that firms invest in products new to the firm increases from under 1 percent for politically connected firms to over 7 percent for unconnected firms. The results are robust across different innovation measures. Despite innovating less, politically connected firms are more capital intensive, as they face lower marginal cost of capital due to the generous policy privileges they receive, including exclusive access to input subsidies, public procurement contracts, favorable exchange rates, and financing from politically connected banks. These privileges are largest when compared with their direct competitors operating in the same 4-digit sectors. The findings suggest that connected firms out-rival their competitors by lobbying for privileges instead of innovating. In the aggregate, these policy privileges reduce Egypt's long-term growth potential by diverting resources away from innovation to the inefficient capital accumulation of a few large, connected firms. A wide array of supporting evidence suggests that this effect is causal and not due to selection.